For Whom the Bells Toll: Alonso and a Regional Science of Decline. (March 2018) - Franklin, Rachel S.; van Leeuwen, Eveline S.
In his presidential address to the Regional Science Association over thirty years ago, William Alonso presented the case for "Five Bell Shapes in Development" and argued that "the developed countries will enter fully in to the realm of the right-hand tail of these curves" (p. 16) and that this transition might result in several surprises. He proposed, therefore, that we should study the right tail of these "curves" as well as interactions among them. Much of what Alonso suggested has come to pass, although his prognostications were not always exact. And although he touched on several issues of relevance to regional scientists, the discipline has been slow to move away from a growth-centered paradigm. The strength of regional science—the capacity to consider economic, demographic, and geographical aspects of an issue simultaneously—has yet to be focused on some of the "right-hand" challenges that have arisen, population loss, for example. In this article, we provide a review of regional science research within the context of Alonso's five bells and hypothesize how Alonso's propositions might differ in today's world. We then focus more specifically on one particular area: population loss. Using these examples allows us to highlight how regional science might contribute to the conceptualization of "right-hand tail" development challenges, especially where theory, issues of spatial scale, and interregional dependencies are concerned.